Lina, uma criança exemplar! Friedrich Froebel e a pedagogia dos jardins-de-infância - Alessandra Arce (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2002)
This work analyses an important text written by Friedrich Froebel (1782- 1852), creator of the Kindergartens. The text, entitled "On how Lina learnt to read and write: a story for children who like to be busy", explains, in story form, the most important educational principles of Froebel. The aim of this paper is to present the ideas of the author with regard to how one ought to think and practice education for early childhood, taking the story as the starting point. The ideas of one of the pioneers of education for early childhood (children of less than six years of age) are re-discussed since it is considered that his educational theory presents the seeds for current discussions in favour of constructing a Pedagogy for Child Education.